40Ar/39Ar age of the Lonar crater and consequence for the geochronology of planetary impacts - Jourdan, Fred; Moynier, F.; Koeberl, C.; Eroglu, S. (Geological Society of America, 2011)
Asteroid impacts play an important role in the evolution of planetary surfaces. In the inner solar system, the large majority of impacts occur on bodies (e.g., asteroids, the Moon, Mars) covered by primitive igneous rocks. However, most of the impacts recorded on Earth occur on different rock types and are poor proxies for planetary impacts. The Lonar crater is a 1.88-km-diameter, Quaternary age crater (Fig. 1) located on the ca. 66 Ma Deccan basaltic traps in Maharashtra (India), and is one of the very few craters on Earth emplaced directly on basaltic lava flows. We carried out 12 40Ar/39Ar step-heating experiments on 4 melt rock samples in order to (1) obtain a precise age for the Lonar crater; (2) study the response of isotopic chronometers during impacts on mafic target rocks; and (3) better understand the dating of extraterrestrial impact craters. We obtained 10 plateau and 9 inverse isochron ages on various aliquots. Combination of selected data into a global inverse isochron yielded an age of 570 ± 47 ka (MSWD = 1.1; P = 0.24). In comparison, previous nonisotopic investigations on rocks thought to be affected by secondary processes yielded a range of much younger ages (ca. 12–62 ka). The measured 40Ar/36Ar trapped values offer a direct comparison with the atmospheric benchmark value and allow us to test the inherited 40Ar* degassing capacity of basaltic impact melt rocks. The 40Ar/36Ar ratio of 296.5 ± 1.7 is indistinguishable from the atmospheric composition and suggests that inherited 40Ar* is absent from the melt rock. This result substantiates diffusion models that predict a near-complete degassing of low-viscosity melt (e.g., basalts) during impact, and demonstrates for the first time that inherited 40Ar* is less problematic for 40Ar/39Ar dating of impact events in basaltic igneous rocks compared to Si-rich rocks.These results provide direct evidence that basaltic melt rocks are excellent candidates for recording the timing of planetary impact events and, as far as dating is concerned, should be the preferred targets of sample recovery by future missions.